Elimination of intracanal infection in dogs' teeth with induced periapical lesions after rotary instrumentation: Influence of different calcium hydroxide pastes - Soares, Janir Alves; Leonardo, Mário Roberto [UNESP]; Da Silva, Léa Assed Bezerra; Tanomaru Filho, Mario [UNESP]; Ito, Izabel Yoko (FapUNIFESP (SciELO), 2006)
The aim of this study was to evaluate the antiseptic efficacy of rotary instrumentation associated with calcium hydroxide-based pastes prepared with different vehicles and antiseptics. Chronic periapical lesions were experimentally induced in 72 premolar root canals of four dogs. Under controlled asepsis, after initial microbiological sampling (A1), the root canals were instrumented using the ProFile system in conjunction with 5.25% sodium hypochlorite and the intracanal medication was placed. Four experimental groups were formed according to the pastes used: group 1- Calen (n=18), group 2- Calen+CPMC (n=20), group 3- Ca(OH)2 p.a.+ anaesthetic solution (n=16) and group 4- Ca(OH)2 p.a.+ 2% chlorhexidine digluconate (n=18). After 21 days, the pastes were removed; the canals were emptied and 96 hours later a second microbiological sample was obtained (A2). The incidence of positive microbiological cultures and the number of cfus in stages A1 and A2 were compared statistically by the Wilcoxon test while the influence of the different treatments in intracanal infection was evaluated by Kruskal-Wallis test at 5% significance level (p<0.05). Large numbers of strict and facultative anaerobes, and viridans group streptococci were found in 100% of root canals of A1 samples. Among A2 samples, all treatments showed significant reduction of cfus and positive cultures (p<0.05), but only groups 3 and 4 showed 100% of root canals free of microorganisms. Rotary instrumentation plus NaOCl 5.25% associated with intracanal medication produced a drastic reduction or elimination of intracanal microbiota, whose performance was not influenced by the nature of the vehicle or the antiseptic added to the Ca(OH)2 p.a.
Keywords: Calcium hydroxide; Microorganisms; Periapical lesions; Root canal therapy